POLA TABUHAN ALAT MUSIK ENGITAKNG PADA PERAYAAN ADAT NYOBENG SUKU DAYAK SUNGKUNG KECAMATAN SIDING KABUPATEN BENGKAYANG - Yustinus Mangah; Winda Istiandini; Chiristianly Silaban (Universitas Tanjungpura, 2019)
AbstractThe research was distributed by type of traditional musical instruments in the WaSP which is inherited from ancestors that need to be in the guard and developed to study and preserve the tradition music of course there are guide books as a source reference, but the shape of the pattern on the WaSP there is no reference or study guide book on how to play a musical instrument engitakng wasps are good and true. This research is very necessary because there has been no previous research relating to engitakng musical instrument themselves mainly existing in sungkung. The data were analyzed qualitatively, with resource data, Mr. Ayang, Damianus Jina, Ignasius Gisig, several other art artists and actors who play an active role as well as find out about music engitakng music, especially the music of Engitakng Pattern On A Celebration Of Indigenous Dayak Nyobeng Sungkung.Based on data analysis, researchers can be concluded that Engitakng is a traditional musical instrument that is played by the way in at to use beater, in this engitakng music has just played on certain rituals like nyobeng, as a counterpoint to the dance music tradition of the dayak tribe ngigel sungkung. Engitakng music in celebration of indigenous Dayak Sub Sungkung Nyobeng Siding Bengkayang consists of 4 instruments, namely 1. Nagun, 2. Natent nagun, 3. Natent taak, 4. taak. The results of this research are expected to regenerate interest, the spirit of the younger generation to learn the musical traditions and can contribute to the world of education i.e. researchers offer a draft implementation plan-shaped learning Learning (RPP) as an indicator of competency and curriculum of 2013. Keywords: Patterns, Beats, Engitakng, Nyobeng